The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jcmm.15704
|View full text |Cite
|
Sign up to set email alerts
|

BDNF promoted osteoblast migration and fracture healing by up‐regulating integrin β1 via TrkB‐mediated ERK1/2 and AKT signalling

Abstract: Brain‐derived neurotrophic factor (BDNF) has been reported to participate in fracture healing, whereas the mechanism is still unclear. Since osteoblast migration is important for fracture healing, investigating effects of BDNF on osteoblasts migration may help to reveal its mechanism. Here, MC3T3‐E1 cells were used in vitro while closed femur fracture mice were applied in vivo. Cells migration was assessed with Transwell assay. The protein expression was analysed by immunoblotting. X‐ray and Micro‐CT were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…BDNF promoted multiple cells proliferation including trophoblastic cell [ 32 ], oligodendrocyte precursors [ 33 ] and schwann cells [ 34 ]. Zhang et al [ 35 ] also found that BDNF could promoting osteoblast migration through ERK1/2 and Akt signaling pathway. Borghesani et al [ 36 ] revealed that BDNF is directly motogenic for granule cells and provides a directional cue promoting migration from the granule cell layer to the internal granule cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF promoted multiple cells proliferation including trophoblastic cell [ 32 ], oligodendrocyte precursors [ 33 ] and schwann cells [ 34 ]. Zhang et al [ 35 ] also found that BDNF could promoting osteoblast migration through ERK1/2 and Akt signaling pathway. Borghesani et al [ 36 ] revealed that BDNF is directly motogenic for granule cells and provides a directional cue promoting migration from the granule cell layer to the internal granule cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the promotion effect of BDNF on osteoblast migration and fracture healing is also via TrkB. The specific inhibitor for Trks, K252a, can suppress BDNF-induced cell migration, integrin β1 expression and activation of ERK1/2 and AKT signaling pathways (Zitao Zhang et al, 2020). We thus hypothesized that TrkB is the link between 7,8-DHF and Wnt/β-catenin reinforcement during osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, some researches confirmed that BDNF plays a positive role in accelerating bone union ( Kauschke et al, 2018a ; Kauschke et al, 2018b ; Liu et al, 2018 ). Recently, a study provided further understanding for the underlying mechanism of BDNF in fracture healing that BDNF contributed to MC3T3-E1 migration and increased the expression level of integrin β1 ( Zhang et al, 2020 ). Considering the fact that 7,8-DHF mimics so many aspects of BDNF, we hypothesized that there may be a regulatory network involving 7,8-DHF and bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] BDNF is an important regulator of nervous system, [ 14 , 15 ] and also participates in the regulation of bone tissues. [ 16 , 17 ] Nose and coworkers found that serum BDNF level was positively correlated with BMD, and that it was elevated by estradiol therapy in female osteoporosis patients. [ 18 ] BDNF knockout could inhibit osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%